e-Pirates of the digital age copyright issues in software and music - Dove, Luke; Kyredis, Katrina; Video Education Australasia (Australia : Video Education Australasia, 2008)
'This program examines the complex world of digital piracy and the copyright of computer-related media, including software, games and music. A must see program for students of this digital age.'--Container
DVD format
Keywords: Piracy (Copyright); Software piracy; Music and the Internet